THE USE OF MEDICAL AND PHYTOTHERAPIC PLANTS IN BRAZILIAN PUBLIC HEALTH. - Campos , João Marcelo; Lemos , Paulo Henrique (Brazilian Journal of Implantology and Health Sciences, 2023)
Medicinal plants are used for the purpose of promoting quality of life, even from primordial times. This paper aimed to present the importance of the use of herbal medicines in the network public health. The practice and consumption of herbal medicines has been growing every year, with the emergence of Ordinance No. 971 of May 3, 2006 approving the National Policy for Integrative and Complementary Practices (PNPIC) in Unified Health System (SUS). But there is still a big factor to be overcome, the high requirement of the National Agency Health Surveillance Authority (ANVISA), for the production, marketing and distribution of herbal medicines in the SUS. THE Ordinance GM / MS No. 533 of March 28, 2012 (National List of Essential Medicines - RENAME), cast herbal medicines in Primary Care, consists of only 12 plant species of interest of SUS, considered low due to Brazil being considered one of the countries with the greatest biodiversity in the world. The main problems that hindering the advances of herbal products in the SUS are the lack of state and municipal public policies and the lack of of interest of the managers of these secretariats in complying also with the federal legislation in force.